Penggelapan Motor Rental sebagai Kejahatan Bermotif Ekonomi: Studi Kriminologis di Pangkalpinang - Dimas Andrian Setia Pratama; Maura Pratiwi; Muhammad Sayid Qoumil; Saslina Aulia Rizkya; M. Adha Al Kodri (MAN 4 Kota Pekanbaru, 2026)
This study examines rental motorcycle embezzlement as an economically motivated crime through a criminological perspective, focusing on a case in Pangkalpinang, Indonesia. The study aims to analyze the economic motives underlying the crime, the modus operandi employed by the offender, and the fencing network involved in the distribution of stolen property. This research adopts a qualitative documentary case study approach using secondary data derived from official police documents. The findings indicate that economic pressure served as the primary motive driving the offender to commit embezzlement. The crime was carried out through a trust-based manipulation strategy in which the offender obtained the motorcycle under the guise of a legitimate rental arrangement before converting it into cash through a series of pawn and resale transactions. The findings also reveal that the offense was sustained by an informal distribution network involving multiple actors who facilitated the circulation of illegally acquired assets. These results suggest that rental motorcycle embezzlement should not be viewed merely as an individual criminal act but as part of a broader economic crime ecosystem shaped by the interaction of economic motivation, rational decision-making, and opportunity structures. The study highlights the importance of strengthening verification procedures in rental businesses and improving oversight of informal vehicle transactions to reduce opportunities for economically motivated crimes.